AB0777 PSA PATIENTS REACHING MINIMAL DISEASE ACTIVITY5/7 IMPROVE IN ALL FIELDS OF PSAID. (June 2019) - Pinto-Tasende, Jose; Ventin, Clara; Caeiro, María; Seijas, Alvaro; Aguirre, Rodrigo; Silva, Maria Teresa; Blanco, Francisco
Abstract : Background: Patients with psoriatic arthritis (PsA) show impact on physical and psychological aspect of the disease and it can be measured with the PsA Impact of Disease (PsAID) questionnaire. Impact of disease should improve if patient reach a minimal disease activity (MDA). Objectives: To assess the association between MDA and PsAID questionnaire in patients with PsA from daily clinical practice. Methods: A cross-sectional study was carried out in consecutive patients who fulfilled CASPAR criteria and who were treated according to routine clinical practice (EULAR/GRAPPA recommendations). Patients were considered in MDA if they met at least 5/7 of the MDA criteria. PsAID was also recorded. Continuous variables were reported as median (Q1-Q3). Categorical variables were reported as percentages and frequencies. All analyses were performed using SPSS software. Differences were considered statistically significant if p<0.05 (two tailed). Results: Seventy-two patients were included, 40 males (55.6%), median of age 53.5 years old (47.0-62.7) and disease duration 5 years (3-10). Obesity was 29.6% and C-RP level was 0.31mgr/dl (0.10-0.97). Patient treatments were: NSAID 22.2%, corticosteroids 31.9%, csDMARD 55.6% and biological therapy 20.8%. DAPSA was 9.0 (2.2-19.4) being in VLDA (0-4) 37.5%, LDA (5-14) 22.2%, MDA (15-28) 30.6% and HAD (>28) 9.7%. Patients in MDA 5/7 state were 36 (50%) and median of total score of PsAID was 4.70 (0.85-9.40). All fields of PsAID improved if they reached MDA 5/7 (p <0.01). MDA 5/7 was also related to age, duration of the disease, CRP and DAPSA (see table). Conclusion: Fifty percent of PsA patients achieve MDA in daily clinical practice. MDA patients had a significantly lower impact of the disease according to PsAID. References: [1] Queiro R, et al. Arthritis Res ther. 2017Mar29;19(1):72. Acknowledgement: Sociedade Galega de Reumatoloxía Disclosure of interests: Jose Pinto-Tasende Speakers bureau: Janssen, Novartis, Celgene, BMS, abbvie, Pfizer, Clara Ventin: None declared, María Caeiro: None declared, alvaro Seijas: None declared, Rodrigo aguirre: None declared, Maria Teresa Silva: None declared, Francisco Blanco Speakers bureau: Celgene, Pfizer, abbvie